TRADISI PESANTREN: MENGEMBANGKAN MANAJEMEN MODEL PEMBELAJARAN KITAB KUNING UNTUK MENINGKATKAN MINAT BELAJAR SANTRI DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Nahdliyah , Amirotun; Jamroh, Nur Maya Badriyatul (International Conference on Humanity Education and Society (ICHES), 2024)
Islamic boarding school is an educational institution that focuses on religious education in order to improve the quality of religious knowledge of students in Islamic boarding schools. The study of the yellow book is an important component in Islamic boarding schools. Therefore, the Islamic Boarding School makes every effort to organize and manage the study of the Yellow Book in order to increase the awareness and interest of the students in studying the Yellow Book widely and in depth. At the Darussalam Islamic Boarding School, apart from synergizing with the Madrasah Diniyyah, there is the Polarussalaf Recitation Institute (Ma'hadiyyah in nature) which houses several Institute departments that specifically study the Yellow Book. Among them: Sorogan, Akbar Recitation, Maktabah, Ihfadz, Mufidah. This research aims: 1) to determine the manajement learning process of the yellow book at the Suhussalaf Study Institute at the Darussalam Islamic Boarding School Blokagung Banyuwangi. 2) to determine students' interest in studying the yellow book at the Darussalam Islamic Boarding School Blokagung Banyuwangi. 3) to determine the Islamic Boarding School's efforts to increase interest in learning the yellow book among students at the Darussalam Islamic Boarding School Blokagung Banyuwangi. The research method is descriptive qualitative, the research location is at the Darussalam Islamic Boarding School Foundation, Blokagung Banyuwangi. Data collection techniques: interviews, observation, and documentation. Data analysis uses interactive analysis models including data reduction, data presentation, and drawing conclusions. Validity test uses data triangulation techniques. The results of the research include: 1) the yellow book learning process at the Darussalam Islamic Boarding School Blokagung Banyuwangi. Each department at the Polarussalaf Recitation Institute has implemented an administration model of learning activities, including: planning, organizing, implementing and evaluating/observing learning. The learning activity model is designed starting from input, process transformation, to output of learning activities. 2) students' interest in learning to study the yellow book at the Darussalam Islamic Boarding School Blokagung Banyuwangi, factors that influence students' interest in learning are internal and external influences from the students, but it was found that the reason why students are less interested in participating in these activities is the large amount of educational focus in the Islamic boarding school, including: focus on formal education, mujadi education, and tahfidzul Qur'an education. 3) Pesantren's efforts to develop interest in studying the Yellow Book among students, including: 1) giving students the option to study topics of their interest. 2) create an effective and enjoyable learning climate. 3) using interactive recitation models.